Silver Nitrate: A Catalyst for Unprecedented in vitro Development of Spathiphyllum wallisii, an Important Ornamental Plant - Boudadi Imane; Lachguer Khadija; El Merzougui Soumaya; El Boullani Rachida; Lagram Khalid; Serghini Mohammed Amine (Journal of Horticultural Research)
The ornamental plant Spathiphyllum wallisii is becoming increasingly popular worldwide, and tissue culture is regarded as a practical option for its massive production. Following the multiplication phase and successive subcultures for an extended period, some morphological changes in shoots were observed in Spathiphyllum explants, primarily a reduction in leaf area. For the first time, we report the application of silver nitrate to enhance Spathiphyllum shoot and root quality. The Murashige and Skoog (MS) medium, with 30 g·L−1 of sucrose and 100 mg·L−1 of ascorbic acid, was supplemented with different concentrations of AgNO3. The addition of AgNO3 improved shoot development and leaf expansion by increasing their length and width. Specifically, at the 2.0–4.0 mg·L−1 range, silver nitrate successfully induced the highest leaf area (1.7 cm2), while stem elongation was promoted with the application of 3.0 mg·L−1 of AgNO3. Additionally, optimal leaf numbers of new shoots were observed at 1 mg·L−1. Furthermore, when used at an optimal concentration, AgNO3 significantly boosted rhizogenesis, increasing the number (9.2 roots), length (5.8 cm), and diameter (1 mm) of roots per explant. After the plantlets were transferred to pots, they acclimatized successfully with a 100% survival rate. This finding underscores the potential of silver nitrate to optimize the growth and rooting of Spathiphyllum shoots, paving the way for a more efficient micropropagation process.